التصوير المشهدي في شعر حسن سالم الدباغ - عجيل صاحي الهاشمي كريم (Journal of College of Education, 2022)
This critical approach deals with the poetry of Hassan Salem Al-Dabbagh in an attempt to investigate the nature of the relationship between the different arts, in light of the openness of the modern poetic text to the various neighboring arts. The research came to shed light on an important tool of cinematic art represented by scenic photography, and it became clear that this employment was a flexible tool in the poetic fabric of its various poetic texts. The nature of the study in this approach necessitated the pursuit of scenic photography at multiple levels, the most prominent of which was descriptive scenic photography, which approached the modalities of scenic photography by adopting descriptions accompanied by effects that furnish the scene in order to achieve an integrated scenic structure. Then the study dealt with scenic narrative photography, using tales of various forms as a method for scenic embodiment. It became clear that the poet employed many realistic tales to present his pictorial scene.The share of dialogic scenery was present in this study, and the poet relied on various dialogues in making scenes that overlapped with cinema